What is the Role of the Anti-Parasitic Drugs in the Treatment of Coronavirus Disease 2019? - Rahmati Roodsari, Sara; Arab-Mazar, Zahra (Novelty in Biomedicine, 2020)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a rapidly emerging viral infection causing coronavirus disease 2019 (COVID-19). The first report of the novel coronavirus, SARS-CoV-2, originated in Wuhan, China, in early December 2019 . Currently, there are no U.S. Food and Drug Administration (FDA)–approved drugs for the treatment of patients with COVID-19. A great deal of effort is ongoing to find effective therapeutics and preventive measures against this transmissible virus with high mortality. As result, available data are limited, and there are minimal randomized controlled trial (RCT) data on the efficacy of antiviral or immunomodulatory agents for the treatment of COVID-19 . Most of the treatment protocols are based on observational studies and anecdotic reports.